HOW ZOOYNYMS ARE USED IN METAPHORICAL UNDERSTANDING - Ahmedova Nodira Djavadullaevna (Modern American Journals, 2025)
This article explores the zoonyms and the usage of zoonyms in metaphorical understanding. The place, the role of zoonyms in linguistic area as well as in culture, history and language are also discussed with clear examples and explanations
Keywords: Zoonyms, Metaphor, metaphorical expression, social role, human behavior, cognitive and linguistic significance, ethnolinguistic heritage.